Myocardial remodeling in diabetic cardiomyopathy associated with cardiac mast cell activation. - Zhi Gang Huang (Public Library of Science (PLoS), 2013)
Diabetic cardiomyopathy is a specific disease process distinct from coronary artery disease and hypertension. The disease features cardiac remodeling stimulated by hyperglycemia of the left ventricle wall and disrupts contractile functions. Cardiac mast cells may be activated by metabolic byproducts resulted from hyperglycermia and then participate in the remodeling process by releasing a multitude of cytokines and bioactive enzymes. Nedocromil, a pharmacologic stabilizer of mast cells, has been shown to normalize cytokine levels and attenuate cardiac remodeling. In this study, we describe the activation of cardiac mast cells by inducing diabetes in normal mice using streptozotocin (STZ). Next, we treated the diabetic mice with nedocromil for 12 weeks and then examined their hearts for signs of cardiac remodeling and quantified contractile function. We observed significantly impaired heart function in diabetic mice, as well as increased cardiac mast cell density and elevated mast cell secretions that correlated with gene expression and aberrant cytokine levels associated with cardiac remodeling. Nedocromil treatment halted contractile dysfunction in diabetic mice and reduced cardiac mast cell density, which correlated with reduced bioactive enzyme secretions, reduced expression of extracellular matrix remodeling factors and collagen synthesis, and normalized cytokine levels. However, the results showed nedocromil treatments did not return diabetic mice to a normal state. We concluded that manipulation of cardiac mast cell function is sufficient to attenuate cardiomyopathy stimulated by diabetes, but other cellular pathways also contribute to the disease process.